Growth performance of Tilapia (Oreochromis niloticus) cultivated in water from ex-sand pit lakes by phytoremediation treatments - Henni Wijayanti Maharani; Qadar Hasani; Muhammad Ariful Aimma; Deny Sapto Chondro Utomo; Limin Santoso; Nidya Kartini; Radho Al Kausar (Journal of Degraded and Mining Lands Management, 2022)
Utilization of ex-sand pit lakes for aquaculture is difficult due to low water quality and high concentrations of iron (Fe). Phytoremediation using aquatic plants has been proven to be effective in reducing Fe in waters. This study aims to determine the growth, feed conversion efficiency and survival rate of tilapia (Oreochromis niloticus) cultured with ex-sand mining water media with phytoremediation treatment. Phytoremediation treatment was carried out by Eichhornnia crassipes, Azolla pinnata, and Salvinia molesta. Fish culture experiments were carried out in plastic tarpaulin tanks for 40 days, with ad satiation feeding, three times a day using the commercial feed. The results showed that phytoremediation with aquatic plants had succeeded in reducing Fe to a level suitable for fish culture. Fish culture experiments showed an absolute length growth rate of 0.09-0.18 cm/day and an absolute weight growth rate of 0.11-0.16 g/day. The feed conversion ratio was 1.18-1.40 and the survival rate was 98.04-99.08%. The survival rate of tilapia is high, the feed conversion ratio is medium and growth is low. The high environmental temperature and the decrease in water quality due to the absence of water changes and aeration are suspected of causing the low growth of fish. Therefore, further research with water change and aeration experiments and the use of other species of fish is needed to follow up the results of this study.